Rancang Bangun Aplikasi Pencarian Bengkel Aktif Berbasis Google Maps Api di Wilayah Kota Makassar - Mutmainna; Andi Mashdarul Khair (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2022)
The rise of vehicle users in Makassar City mostly requires maintenance and repairs when the vehicle has a problem. Searching for a location is one of the most discussed problems at this time. The number of workshops spread in Makassar City is not comparable with information about its location. In order to make it easier for people to find and reach a location from a workshop, the location search process can be done by utilizing technology from the Google Maps API where we can see the location of the workshop. Therefore, it is necessary to have an application that can provide information about the location of the workshop that is still open that is around us, which later makes it easier for us to know which workshop is still open and closest to our location.